Usulan Strategi Pemasaran Kendaraan Bermotor Di Dealer Citra Abadi Motor Dengan Pendekatanquantitative Strategic Planningmatrix (Qspm)(Studi Kasus: Dealer Citra Abadi Motor Jl. Raya Pajang - Gawok Km7) - Pambudi, Tri Setyo; , Etika Muslimah, S.T., M.M., M.T; , Siti Nandiroh, S.T., M.Eng (2015)
Citra Abadi Motor dealers are dealers selling motorcycles traded half-life. In 2014 dealers experienced a decrease in sales, while the factors - factors that affect the quality of the motor half-life is less good, emerging new motorcycles, and competitors. The aim of this study is to formulate appropriate development strategy planning and to determine the company's development strategy planning priorities. In this study the methods used SWOT and Quantitative Strategy Planning Matrix (QSPM) to analyze the internal and external factors. The analysis is conducted to determine the strengths, weaknesses, opportunities, and threats. IFE factor analysis (2.71) and EFE (2.88) to determine the position of the company today is the V quadrant ie Hold and Maintain (keep and maintain). Preparation of the strategy carried out by analyzing the factors strengths, weaknesses, opportunities and threats SWOT matrix. SWOT analysis produced 10 alternative development strategies. Alternative strategies are analyzed using matrix Quantitative Strategy Planning Matrix (QSPM) to find an alternative strategy that has the highest score of the attraction. Results of analysis using matrix Quantitative Strategy Planning Matrix (QSPM) shows that the strategy of increasing the promotion of an alternative strategy that scores the highest interest. The second strategy which can be applied next is to expand market share. Keywords: Strategy, Quantitative Strategy Planning Matrix (QSPM), SWOT